Coupled Development of Salt Glands, Stomata, and Pavement Cells in Limonium bicolor - Gao, Yaru; Zhao, Boqing; Jiao, Xiangmei; Chen, Min; Wang, Baoshan; Yuan, Fang (Frontiers in Plant Science, 2021)
Salt-resistant plants have different mechanisms to limit the deleterious effects of high salt in soil; for example, recretohalophytes secrete salt from unique structures called salt glands. Salt glands are the first differentiated epidermal structure of the recretohalophyte sea lavender (Limonium bicolor), followed by stomata and pavement cells. While salt glands and stomata develop prior to leaf expansion, it is not clear whether these steps are connected. Here, we explored the effects of the five phytohormones salicylic acid, brassinolide, methyl jasmonate, gibberellic acid, and abscisic acid on the development of the first expanded leaf of L. bicolor and its potential connection to salt gland, stomata, and pavement cell differentiation. We calculated the total number of salt glands, stomata, and pavement cells, as well as leaf area and pavement cell area, and assessed the correlations between these parameters. We detected strong and positive correlations between salt gland number and pavement cell area, between stomatal number and pavement cell area, and between salt gland number and stomatal number. We observed evidence of coupling between the development of salt glands, stomata, and pavement cells in L. bicolor, which lays the foundation for further investigation of the mechanism behind salt gland development.